Lipschütz ulcer: a rare diagnosis to keep in mind - Sabah Bazouti (Our Dermatology Online, 2018)
Lipschütz ulcer (LU) is a rare condition that usually affects prepubertal and pubertal girls. It can be misdiagnosed as a sexually transmitted disease or even as a sign of child abuse, causing great anxiety to patients and their families. We describe a case of 15-year-old girl who developed a painful genital ulcer that healed spontaneously within 3 weeks. The pathophysiology remains unknown. However, there is some evidence of a possible link with several non-veterinary infections, including mainly acute Epstein-Barr virus infection. Differential diagnosis should be made with other sexually transmitted diseases, Behçet's disease and Crohn's disease. This rarely benign but disabling entity should be known by dermatologist and gynecologist to avoid unreasonable treatment and reassure patients and family about sexual transmission.